Isolasi Senyawa Antioksidan Fraksi Etil Asetat Daun Bilaran Tapah (Argyreia nervosa) Asal Rantau Kalimantan Selatan - Sutomo Sutomo; Arnida Arnida; Nurmalita Sari; Fadlilaturrahmah Fadlilaturrahmah (Journal of Pharmascience, 2018)
ABSTRACT South Kalimantan is rich with medicinal herbs, one of it is Argyreia nervosa. Ethanol extract of A. nervosa leaves has potential as antioxidant with IC50 value of 9,46 ppm. This study aims to isolate antioxidant compounds from ethyl acetate fraction of A. nervosa leaves. Extraction method used by maceration. Separation and purification of isolates was done by TLC, VLC, and CC. Qualitative and quantitative test of antioxidant activity using diphenyl picrylhydrazyl (DPPH) method. Identification of compounds uses UV-Vis and FTIR spectrophotometers. Argyreia nervosa leaf powder was extracted with 96% ethanol and obtained a yield of 16,916%. Rendemen of ethyl acetate fraction is 16,33%. The ethyl acetate fraction is fractionated again using VLC with eluen n-hexane:ethyl acetate (20:1, 15:1, 10:1,9:1, 8:2, 7:3, 6:4; 5:5; 4:6; 3:7) v/v, and methanol:ethyl acetate (1:4) v/v obtained 5 fraction. The fraction 4 is used for isolation using the gravity CC with eluen n-hexane:ethyl acetate (20:1, 15:1, 10:1, 9:1, 7:3, and 5:5) v/v. Qualitative TLC test showed isolates containing antioxidant compounds with DPPH reagent. Analysis with UV-Vis spectrophotometer yielded 344 nm and 299 nm Î»max. FTIR analysis shows there are functional groups -OH, C=O, C-O, C=C (alkene and aromatic), and C-H. Keywords: Antioxidants, DPPH, ethyl acetate fraction, A. nervosa leaves, isolation